Electromyography as a Means of Assessing Masticatory Muscle Activity in Patients with Pain-Related Temporomandibular Disorders - Liliana Szyszka-Sommerfeld; Monika Machoy; Mariusz Lipski; Krzysztof Woźniak (Pain Research and Management)
Aim. The aim of this study was to evaluate masticatory muscle electrical activity in patients with pain-related and pain-free temporomandibular disorders (TMDs) as well as in subjects with no TMD. Methods. Ninety children with mixed dentition were recruited to the study. Of this total, 30 subjects were diagnosed with pain-related TMD (TMD-P), 30 with pain-free TMD (TMD-PF), and 30 without TMD. We used Axis I of the Research Diagnostic Criteria for TMD (RDC/TMD) to assess the presence of TMD in the examined children. The electromyographical (EMG) potentials of the temporalis and masseter muscles were measured with a DAB-Bluetooth Instrument (Zebris Medical GmbH, Germany) at rest and during maximum voluntary clenching (MVC). Results. An analysis of the EMG recordings showed statistically significant intergroup differences in masticatory muscle electrical activity at rest and during MVC. Significantly higher rest temporalis muscle activity was noted in pain-related TMD subjects compared with that children from the pain-free TMD and non-TMD groups, as well as in TMD-PF children in relation to those without TMD. The EMG potentials of the temporalis muscle during MVC were much lower in patients with TMD-P than in pain-free TMD and non-TMD subjects. Masseter muscle activity at rest in the TMD-pain group was significantly greater, and masseter muscle EMG potentials during clenching were markedly lower than in patients with no TMD diagnosis. Conclusion. The use of electromyography to assess masticatory muscle function revealed alterations in the pattern of temporalis and masseter muscle activity in patients with pain-related TMD compared with the pain-free subjects.